N $$ \mathcal{N} $$ = 3 conformal superspace in four dimensions - Sergei M. Kuzenko; Emmanouil S. N. Raptakis (Journal of High Energy Physics, 2024)
Abstract We develop a superspace formulation for N $$ \mathcal{N} $$ = 3 conformal supergravity in four spacetime dimensions as a gauge theory of the superconformal group SU(2, 2|3). Upon imposing certain covariant constraints, the algebra of conformally covariant derivatives ∇ A = ∇ a ∇ α i ∇ i α ⋅ $$ {\nabla}_A=\left({\nabla}_a,{\nabla}_{α}^i,{\nabla}_i^{\overset{· }{α }}\right) $$ is shown to be determined in terms of a single primary chiral spinor superfield, the super-Weyl spinor W α of dimension +1/2 and its conjugate. Associated with W α is its primary descendant B i j of dimension +2, the super-Bach tensor, which determines the equation of motion for conformal supergravity. As an application of this construction, we present two different but equivalent action principles for N $$ \mathcal{N} $$ = 3 conformal supergravity. We describe the model for linearised N $$ \mathcal{N} $$ = 3 conformal supergravity in an arbitrary conformally flat background and demonstrate that it possesses U(1) duality invariance. Additionally, upon degauging certain local symmetries, our superspace geometry is shown to reduce to the U(3) superspace constructed by Howe more than four decades ago. Further degauging proves to lead to a new superspace formalism, called SU(3) superspace, which can also be used to describe N $$ \mathcal{N} $$ = 3 conformal supergravity. Our conformal superspace setting opens up the possibility to formulate the dynamics of the off-shell N $$ \mathcal{N} $$ = 3 super Yang-Mills theory coupled to conformal supergravity.